The structure of Get4 reveals an α-solenoid fold adapted for multiple interactions in tail-anchored protein biogenesis - Bozkurt, Gunes; Wild, Klemens; Amlacher, Stefan; Hurt, Ed; Dobberstein, Bernhard; Sinning, Irmgard (FEBS letters, 2010)
Tail-anchored proteins play important roles in protein translocation, membrane fusion and apoptosis. They are targeted to the endoplasmic reticulum membrane via the guided-entry of tail-anchored proteins (Get) pathway. We present the 2 Å crystal structure of Get4 which participates in early steps of the Get pathway. The structure shows an α-solenoid fold with particular deviations from the regular pairwise arrangement of α-helices. A conserved hydrophobic groove accommodates the flexible C-terminal region in trans. The structural organization of the Get4 helical hairpin motifs provides a scaffold for protein-protein interactions in the Get pathway.
Gesehen am 15.02.2023